EFEKTIVITAS LIMBAH CAIR PERTANIAN SEBAGAI MEDIA PERBANYAKAN DAN FORMULASI Bacillus subtilis SEBAGAI AGENS HAYATI PATOGEN TANAMAN - Khaeruni, Andi; Asrianti, Asrianti; Rahman, Abdul (Jurnal Agroteknos, 2013)
This study aimed to find the best medium for formulation and storage of B. subtilis. The study consisted of two phases: (1) Selection of agricultural wastes as a propagation medium for Bacillus subtilis, (2) test for the stability of Bacillus subtilis in material formulation and  its  inhibition  activity  against Rhizoctonia solani.  The  second  phase  was conducted based on completely randomized design, consisting of five treatments, namely: 100  %  medium  synthetic,  100%  coconut  water,  75%  coconut  water  +  25  %  synthetic medium, 50% coconut water + 50% synthetic medium and 25% coconut water + 75% synthetic medium. Each treatment was repeated three times, so that there were 15 experimental units. B. subtilis ST21e isolate was formulated in liquid medium according to treatment and kept in plastic container at room temperature for 8 weeks to count the number of colonies and inhibition activity every 2 weeks. The results showed that the agricultural wastes (coconut water, tofu water and molasses) can be used as a media for B. subtilis  ST21e  propogation  in  different  cell  growth  pattern.  B.  subtilis  propogation  in medium  coconut  water  +  10% TSB  had the  best growth pattern compared to the  other media. On the other hand, medium containing 25% coconut water + 75% synthetic medium was the best combination for storage medium of  B. subtilis ST21e. Key words: biological agents, Bacillus subtilis, agricultural waste